A Propensity Score–Matched Analysis of Inflammatory Response With Endovascular Aneurysm Sealing vs Endovascular Aneurysm Repair. (October 2017) - Berg, Patrick; Stroetges, Roland A.; Miller, Larry E.; Schoefferle, Jochen
Purpose: To evaluate the risk of postimplantation syndrome associated with endovascular aneurysm sealing (EVAS) and endovascular aneurysm repair (EVAR) in patients treated for abdominal aortic aneurysm (AAA).Methods: From December 2013 to May 2015, 41 AAA patients treated with EVAS (mean age 72±9 years; 38 men) and 63 with EVAR (mean age 74±10 years; 55 men) at a single center were retrospectively reviewed. To control for treatment selection bias, propensity score matching was used to compare outcomes by treatment mode. Main outcomes were postimplantation syndrome (defined as temperature >38°C and leukocyte count >12, 000/µL), inflammatory response markers [platelets and high-sensitivity C-reactive protein (hs-CRP)], and clinical complications through 30 days.Results: In 39 matched patients per group, the incidences of postimplantation syndrome (p=0.07), mean body temperature (p=0.05), mean leukocyte count (p=0.003), and mean hs-CRP (p<0.001) were proportionally lower with EVAS vs EVAR. Serious adverse events (0% vs 12.8%, p=0.05) and endoleaks (0% vs 10.3%, p=0.13) through 30 days were less frequent with EVAS, but the group differences were not significantly different. The choice of endovascular graft material influenced postoperative and 30-day clinical outcomes, with greater overall risk observed with polyester stent-grafts.Conclusion: Endovascular aneurysm sealing is associated with a blunted systematic inflammatory response compared with EVAR. Polyester stent-grafts induce the greatest periprocedural inflammatory response.